2D Ca3Sn2S7 Chalcogenide Perovskite: A Graphene‐Like Semiconductor with Direct Bandgap 0.5 eV and Ultrahigh Carrier Mobility 6.7 × 104 cm2 V−1 s−1. Issue 51 (4th November 2019) - Du, Juan; Shi, Jun‐jie
Abstract: Graphene, a star 2D material, has attracted much attention because of its unique properties including linear electronic dispersion, massless carriers, and ultrahigh carrier mobility (10 4 –10 5 cm 2 V −1 s −1 ). However, its zero bandgap greatly impedes its application in the semiconductor industry. Opening the zero bandgap has become an unresolved worldwide problem. Here, a novel and stable 2D Ruddlesden–Popper‐type layered chalcogenide perovskite semiconductor Ca3 Sn2 S7 is found based on first‐principles GW calculations, which exhibits excellent electronic, optical, and transport properties, as well as soft and isotropic mechanical characteristics. Surprisingly, it has a graphene‐like linear electronic dispersion, small carrier effective mass (0.04 m0 ), ultrahigh room‐temperature carrier mobility (6.7 × 10 4 cm 2 V −1 s −1 ), Fermi velocity (3 × 10 5 m s −1 ), and optical absorption coefficient (10 5 cm −1 ). Particularly, it has a direct quasi‐particle bandgap of 0.5 eV, which realizes the dream of opening the graphene bandgap in a new way. These results guarantee its application in infrared optoelectronic and high‐speed electronic devices. Abstract : A novel and stable 2D Ruddlesden–Popper‐type layered chalcogenide perovskite semiconductor, Ca3 Sn2 S7, with graphene‐like linear electronic dispersion, small carrier effective mass (0.04 m0 ), and ultrahigh carrier mobility (6.7 × 10 4 cm 2 V −1 s −1 ), Fermi velocity (3 × 10 5 m s −1 ), and optical absorption coefficient (10 5 cm −1 ), is found. Particularly, its direct quasi‐particle bandgap of 0.5 eV realizes the dream of opening the graphene bandgap in a new way.